1964
DOI: 10.1177/12.4.288
|View full text |Cite
|
Sign up to set email alerts
|

Acid Phosphatase in Carcinoma of the Prostate in Man

Abstract: Quantitative histochemistry of the human prostate demonstrates that in microtome sections of equal protein content the acid phosphatase activity is proportional to the number of acini present. The occurrence of cancer in these acini results in a profound lowering of the acid phosphatase activity. We postulate that the normal cell that evolves slowly into the cancer cell and highly differentiated carcinoma subsequently becomes undifferentiated and metastasizes. Finally, it is suggested that some change in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…Both studies showed a lower activity in cancer cells than in hyperplastic cells. This is in agreement with earlier results (Marberger, 1956;Woodard, 1956;Parkin et al, 1964;Kirchheim et al, 1964;Brandes and Bourne, 1956). The histochemically demonstrated absence of amino-peptidase activity in prostatic carcinomatous tissue was discussed by Kirchheim as a criterion of malignancy (Kirchheim et al, 1966).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Both studies showed a lower activity in cancer cells than in hyperplastic cells. This is in agreement with earlier results (Marberger, 1956;Woodard, 1956;Parkin et al, 1964;Kirchheim et al, 1964;Brandes and Bourne, 1956). The histochemically demonstrated absence of amino-peptidase activity in prostatic carcinomatous tissue was discussed by Kirchheim as a criterion of malignancy (Kirchheim et al, 1966).…”
Section: Resultssupporting
confidence: 94%
“…From the literature, there seems to be agreement in the localization of the enzymes, but the amount of activity is discussed and diverging results have been obtained (Parkin et al, 1964;Kirchheim et al, 1964;Mathes and Norman, 1956;Brandes and Bourne, 1956;Feustel et al, 1970;Aso et al, 1968). Additional studies were performed in our investigations.…”
Section: Methodsmentioning
confidence: 97%
“…Weak staining by APG1 was observed in the normal and hyperplastic glands of most sections, but no staining was observed in the carci noma. The frequency of the positive staining for anti-PSAP and anti-PSA was reduced with increasing grade as indicated by a number of reports [11,12], Frozen Sections. The positive staining rate of APG1 was 100% in simple glands, 33% in cribriform and fused glands and 17% in solid and trabecular types, showing a declining frequency of the positive staining with tumor grade ( fig.…”
Section: Immunostainingmentioning
confidence: 92%
“…By contrast, in the same tumours activity of succinic and alpha-glycerophosphate dehydrogenase was reduced. In studies of human prostate cancer, some workers have shown by quantitative histochemical techniques that the level of acid phosphatase activity is reduced as tumour differentiation decreases (Parkin, Bylsma, Torre, Drew, and Madden, 1964). Other histochqmical studies of human cancers have revealed somewhat conflicting results which may be attributed in part to the methodology employed (Dawson, 1967).…”
Section: Discussionmentioning
confidence: 99%